Developing Trainee Translators’ Strategic Subcompetence Through Metacognitive Questionnaires - Fernández, Francesc; Zabalbeascoa, Patrick (Meta, 2012)
This paper presents a case study carried out in a two-part German-Spanish general translation course. It results from a pedagogical intervention aimed at helping first-year translation students to develop their strategic subcompetence through metacognitive questionnaires. It focuses on a single function of this subcompetence, the evaluation of trainees’ translating, which was carried out by using post-translation metacognitive questionnaires. These were meant for trainees to reflect on certain aspects of their translating. The most relevant ones were the identification of translation problems and the justification of their solutions. Both aspects were addressed by a twofold question aimed at helping students to identify adequately-solved problems and to justify their solutions. An analysis of students’ answers to this question reveals that the most frequently identified items were strategically relevant problems to do with general conventions of style and genre-specific expressions. Solutions to these problems were also the most frequently justified, and references to successfully applied translation strategies increased from one part of the course to the other as a trace of gradually developing strategic subcompetence.